A Study on the Usage of Mass Media Information Communication Technology among the Farming Community of Mandya District, Karnataka State, India - Devaraj, Dr.; Kumar, Stanley Madan; Kumari, S. Usha; Machendranath, Dr. (Qualitative and Quantitative Methods in Libraries; Vol 6 No 3 (2017): September 2017 Issue, 2019)
Mass-media plays a very important role in bringing about change in the behavior of users by putting across the useful information, which leads to decision making for adoption of innovation. Among the different Mass-media channels radio and television are becoming popular for farm, home, community and entertainment programmes. This paper discusses the Usage of Mass Media Information Communication Technology among the farming community of Mandya District, Karnataka State, India.